2021
DOI: 10.1016/j.neuroimage.2020.117653
|View full text |Cite
|
Sign up to set email alerts
|

LSD alters dynamic integration and segregation in the human brain

Abstract: Highlights LSD untethers functional connectivity from the constraint of structural connectivity. Increased small-worldness of brain networks predicts LSD-induced ego-dissolution. LSD has time-specific effects on brain network integration and segregation. LSD increases the complexity of segregated brain states. Results bridge pharmacodynamics, subjective experience and brain dynamics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
136
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 130 publications
(160 citation statements)
references
References 102 publications
(190 reference statements)
9
136
1
Order By: Relevance
“…Since diffusion MRI was not acquired as part of the LSD study, the structural connectome used for network control theory analysis was identical to the one used in prior work 5 . Namely, we relied on diffusion data from the Human Connectome Project (HCP, http://www.humanconnectome.org/ ), specifically from 1021 subjects in the 1200-subject release 66 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since diffusion MRI was not acquired as part of the LSD study, the structural connectome used for network control theory analysis was identical to the one used in prior work 5 . Namely, we relied on diffusion data from the Human Connectome Project (HCP, http://www.humanconnectome.org/ ), specifically from 1021 subjects in the 1200-subject release 66 .…”
Section: Methodsmentioning
confidence: 99%
“…This is relevant because the changes in brain function under investigation in the present study arise from the administration of LSD. The serotonin 2a (5-HT2a) receptor is well established as the site responsible for the subjective [13][14][15][16][17] and neural [5][6][7] effects of LSD and other classic serotonergic psychedelics, and this receptor is not uniformly distributed across the brain 46 . Therefore, we sought to determine if the specific regional distribution of 5HT2a receptors in the brain could correspond to especially suitable control points for inducing a reduction in transition energy.…”
Section: Network Control Theory Reveals Lsd-induced Flattening Of the Brain's Energy Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…For example, it has been shown that brain dynamics are significantly altered when consciousness is suppressed by anaesthesia or severe brain injury (Luppi et.al. 2019;Luppi et al, 2020;Huang et al, 2020;Demertzi et al, 2019;Barttfeld et al, 2015), or altered by psychedelics (Atasoy et al, 2017, Lord et al 2019, Luppi et al, 2020c, Luppi et al, 2020d. These results highlight the key role of neural dynamics for consciousness, vindicating the approach adopted by Tononi, Sporns, and Edelman (1998).…”
Section: Decomposing Information Flowmentioning
confidence: 89%